Analysis of Distribution Characteristics and Variation Trends of Organic Matters in Panjiakou Reservoir - LI Kun; ZHAO Xiaohui; LI Kelin; ZHANG Panwei; FANG Deng; FAN Yamin; LIU Xiaoru (Renmin Zhujiang)
In order to understand the improvement of water environment by cage-cleanup-activities in Panjiakou Reservoir,and to find out the types and characteristics of main pollutants in Panjiakou Reservoir,this paper carries out analysis and research on surface water samples in different time and space in the study area.The water samples of Panjiakou Reservoir in 2017 and 2018 are tested by the high-throughput screening technology of full two-dimensional gas chromatography time-of-flight mass spectrometry.The results are further confirmed by the matching degrees,detection rates and other conditions.The confirmed results are classified according to the chemical properties and purposes,and the final results are used to analyze the trend of pollutant species change.Compared with the test results in 2017,there were 244 compounds reduced in 2018,including 38 ketones,27 alkanes,26 phenols,21 ethers,15 organic acids,etc.Among them,25 for industrial intermediates,14 for flavors and fragrances,12 for food additives,8 for industrial use,6 for pharmaceutical products,14 for plasticizers,and so on.Compared with the results in 2017,there were 22 compounds increased in 2018,including 10 esters,3 ketones,2 ethers,1 benzene,1 alcohol, 1 aldehyde,1 organic acid,etc.,among which 5 for flavors and fragrances,4 for plasticizers,2 for intermediates,and 1 for flame retardants,etc.The research indicates that a large number of organic pollutants decreased in the study area from 2017 to 2018,because of the cage-cleanup-activities in this reservoir.